Al-Suhrawardi's Knowledge Construction: A Philosophical Analysis of Illumination, Light, and Isyraqiyah Wisdom - Wahyudi, Dedi; Yunus, Firdaus M. (Jurnal Pemikiran Islam, 2024)
Suhrawardi's Isyraqiyah philosophy emerged as a critique of the perceived limitations within Aristotelian peripatetic philosophy. This study investigates the enduring significance of Suhrawardi’s teachings and their relevance in contemporary philosophical discourse. Employing a qualitative research methodology and an extensive literature review, we analyze Suhrawardi's philosophical contributions towards understanding the complexities of existence. Our findings highlight how Isyraqiyah philosophy promotes tranquility and contemplation, offering a blend of philosophical and spiritual reasoning. This philosophy provides profound insights into the multifaceted nature of existence, guiding individuals in navigating contemporary challenges. Thus, Suhrawardi's Isyraqiyah philosophy remains a vital source of enlightenment and guidance, offering a robust framework for philosophical and spiritual contemplation in modern contexts.